Terminological Patterns and the First Word of the Bible: ב)ראשית) ‘(In the) Beginning’ - Warning, Wilfried (Tyndale bulletin, 2001)
Close reading of the final text of the Pentateuch has brought to light three linguistic linkages based on the nouns ראשהת ‘beginning’, עמר’ Omer’, and אחרית’ end’. According to the text’s extant Endgestalt the two nouns ‘beginning’ and ‘Omer’ overlap in their respective seventh positions, and the two antonyms ‘beginning’ and ‘end’ in the seventh and seventh-from-last/twelfth positions. The conjecture has thus been corroborated that the text has been carefully composed by its ancient author.